Exploring university students’ engagement and motivation: critical factors - Reham Ghanem; Hoda Abdelhameed; Mona Abdulmonem; Rawan Alfrehat; Reem Altaisan; Mona Soliman; Hager Abdel Hadi; Rania Abduljawad; Yousef Alrashed; Nahed Nasr (Institute of Advanced Engineering and Science, 2025)
The study aimed to investigate the critical factors for success students' motivation and their engagement in their learning of Jordan's universities. The quantitative method was employed using a survey questionnaire as the research method to measure students' evaluation of factors. Simple sampling was used to obtain a group of university students. The questionnaire was distributed to 265 university students in Jordan. Data analysis was performed using several analyses such as descriptive analysis, Pearson correlation and regression analysis. The results of the study partially supported several factors influencing students' motivation. The results evidenced that assessment, teaching/learning strategy and students attitudes significantly influenced students learning motivation. The results of this have implications to literature, academicians and decision makers to review and discover the proper methods to invest the necessary tools that can enhance the quality of students learning in the higher education institutions.